Wohnsitutation von Migrantenhaushalten: Eine Analyse mit Blick auf den Effekt der Mietpreisbenachteiligung - Andreas Hartung (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
– In this paper a descriptive overview of the housing situation of immigrants in Germany is combined with a multivariate analysis on potential effects of rental price discrimination for specific groups of immigrants. The driving research question is, whether immigrants systematically pay higher rents for comparable flats. Utilizing data from the German Socio-economic Panel (SOEP) different variables classifying the specific housing situation and regional characteristics are used to ensure the comparability of the rental units. Theoretical argumentation is following the model of price formation on rental markets including the problem of rental-submarket formation as well as the work of Norbert Elias and John L. Scotson on the discrimination of outsiders. The results are predominantly not supporting the theoretically derived hypothesis, which states that Turkish immigrants are in particular exposed to rental price discrimination on the German housing market. However, it also becomes apparent that due to the complexity of the problem a research design which focuses on the entire German housing population is probably not an appropriate one and more detailed and regionally limited analyses would be helpful to explain ethnic-specific discrimination on the housing market.
Keywords: 330; migration; habitation; housing market; consumption; ethnic discrimination